Corporate parenting and corporate entrepreneurship in media company - Ningky Sasanti Munir (International Journal of Financial, Accounting, and Management, 2021)
Purpose; The study aimed to understand how the multi-business company creates value through a combined effort of Corporate Parenting (CP) and Corporate Entrepreneurship (CE). The parenting-fit matrix was used to describe CP, while CE four model was used to describe CE. Research methodology: This study is qualitative applied research using a case study approach conducted on a multi-business media company. Data was obtained primarily through interviews with senior executives representing the holding company and 18 subsidiaries. Questionnaires were also distributed to executives to develop a parenting-fit matrix and CE model. Results: This study shows that the 18 subsidiaries of the multi-business company fall under four different cells. The CE model applied at the parent company level is the enabler. Limitations: The limitation of this study mainly lies in the measurement method's reliability for corporate parenting and corporate entrepreneurship. Contribution: This study shows that, apart from the parent company, the development of new businesses can also be carried out by the subsidiary companies using the CE producer model.